2020
DOI: 10.1128/cmr.00141-20
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug-Induced Tolerance in Mycobacterium tuberculosis

Abstract: SUMMARY Successful treatment of tuberculosis (TB) can be hampered by Mycobacterium tuberculosis populations that are temporarily able to survive antibiotic pressure in the absence of drug resistance-conferring mutations, a phenomenon termed drug tolerance. We summarize findings on M. tuberculosis tolerance published in the past 20 years. Key M. tuberculosis responses to drug pressure are reduced growth rates, metabolic shifting, and the promotion of efflux pump activity. Metabolic shifts upon drug pressure mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(115 citation statements)
references
References 151 publications
1
76
0
18
Order By: Relevance
“…In addition, long-term use of these antibiotics has led to the emergence of drug resistance, which poses a huge threat to human life. MDR and XDR Mtb infections have been reported worldwide ( Seung et al, 2015 ; Sander et al, 2020 ). In this study, we found that orbifloxacin had high anti- Mtb bioactivity in vitro with a low MIC of 0.2 μg/ml and protected the mice from infection in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, long-term use of these antibiotics has led to the emergence of drug resistance, which poses a huge threat to human life. MDR and XDR Mtb infections have been reported worldwide ( Seung et al, 2015 ; Sander et al, 2020 ). In this study, we found that orbifloxacin had high anti- Mtb bioactivity in vitro with a low MIC of 0.2 μg/ml and protected the mice from infection in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics can induce growth and metabolic activity arrest in rapidly growing cells. For example, the antimicrobial effect of INH depends on INH conversion to isonicotinoyl by the catalase-peroxidase katG ( 3 ). Converted isonicotinoyl binds NAD + to make isonicotinoyl-NAD that inhibits mycolic acid synthesis, a bacterial cell wall component, subsequently interfering with mycobacterial cell wall integrity ( 3 ).…”
Section: Mycobacterial Persisters Adapt To Stresses In the Host And Exhibit Antibiotic Tolerancementioning
confidence: 99%
“…The presence of a mycobacterial population with more than one bacterial phenotype has been observed in patients with TB, as indicated by bacterial populations with varying growth dynamics in sputum samples (3). TB treatment strategy involves long-term treatment with several drugs for at least six months, which may increase the risk of MDR-and XDR-Mtb emergence (4)(5)(6), which is attributed to residual bacteria that are sheltered from or unresponsive to antibiotic treatment in heterogenous mycobacterial populations in patients (3). Thus, enhancing treatment success rate, shortening treatment duration, and preventing MDR Mtb emergence are the most critical factors for successful TB treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a deadly infectious disease, tuberculosis (TB) infected about 10 million people and caused an estimated 1.4 million deaths worldwide in 2019, and the responsible pathogen for TB is Mycobacterium tuberculosis ( Mtb ) [ 1 ]. Globally, TB has developed resistance to traditional anti-TB drugs like isoniazid and rifampicin, an unfortunate complication to TB prevention and treatment [ 2 , 3 ]. Patients infected with multidrug-resistant TB (MDR-TB) require medicines at higher costs and a longer time for treatment, only receiving a treatment success rate of 57% [ 1 ].…”
Section: Introductionmentioning
confidence: 99%